Cattle fattening market in Mexico: A network approach - Callejas-Juárez, Nicolás (2024)
Introduction. The network of cattle mobilization for fattening in Mexico is complex. The purpose, volume, origin, and destination of the mobilized animals determine the economic structure and market network. Objective. To analyze the market structure of the national network of cattle for fattening in Mexico from 2017 to 2021. Materials and methods. The study considered all heads of cattle mobilized for fattening in 956 municipalities (supply) and 1173 destination municipalities (demand) within Mexico from 2017 to 2021. The market structure was analyzed using economic, density, and centrality measures from Social Network Analysis (SNA). Results. The network of cattle mobilization for fattening was composed of 31 sources and 32 destinations, with an average annual mobilization of of 3.9 million heads of cattle and 73.6 heads of cattle per mobilization. The most important states in cattle mobilization, both in origin and destination, were Chiapas and Durango. In all cattle sources and destinations, there was a high concentration of fattening steers, as they had low centrality and density measures throughout the network. Veracruz and Durango were the most influential both in origin and destination. Conclusions. The cattle fattening market network in Mexico has a structure with high density and low centrality. The degree of specialization, both in sources and destinations, is low. Supply is concentrated in the southeast, while demand is concentrated in the north and center of the country. This information allows the establishment of three networks: sanitary prevention, cattle traceability, and market information.